C-arm Guided Minimally Invasive Percutaneous Fixation Technique of Mandibular Angle and Ramus Fractures- a Prospective Clinical Study at a Tertiary Care Centre of Odisha, India - Rout, Sourav Kumar (Europasian Journal of Medical Sciences, 2020)
Background: Rigid internal fixation of displaced mandibular angle and ramus fractures often poses a unique challenge to oral and maxillofacial surgeons. Various methods have been published to provide a safe and secure gateway for these circumstances. Intra-oral approach supplemented by a limited percutaneous method of fixation offers a distinct advantage of rigid fixation, reducing the known morbidity of using the sole internal as well as external techniques. The objective was to describe a minimally invasive technique for the mandibular angle and ramus fractures using the combined intraoral and extra-oral approach. Methods: This study was conducted on ten patients with mandibular angle or ramus fractures. All patients underwent open reduction and internal fixation. The intra-oral incision was used for visualization and reduction of fractures, and supplemental percutaneous stab incision was utilized to create a path for insertion of the handheld battery-operated microdrill shaft and screwdriver to permit screws fixation perpendicular to the plates. Results: This combined technique depicted minimal or no soft tissue infections, wound dehiscence, occlusal disturbances, or seventh cranial nerve paralysis. The mean surgical duration was 41.5 minutes. No patient had an visible scar marks, which would require further intervention. Conclusion: The described minimally invasive combined percutaneous and intraoral approach for mandibular angle, and ramus fracture provides a satisfactory alternative which could be safely applied to provide rigid fixation of these fractures with minimal damage to vital structures.